1949
DOI: 10.1111/j.1939-0025.1949.tb05149.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical studies in benign and malignant cases of childhood psychosis (schizophrenia-like).

Abstract: This onset in the first year seemed due to or to coincide with the lackof the normal "confident expectation" of rescue from, or gratification of, the affect hunger by the mother (2) (19).2 In the second crucial period of onset later in infancy (2nd to 5th year), the hitherto narcissistic appersonation of the mother did not suffice any more to counteract the overwhelming anxiety-predisposition. In view of the increased challenge by and requirements of outside reality and the psychosexual conflict in these years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

1953
1953
2004
2004

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(15 citation statements)
references
References 15 publications
1
14
0
Order By: Relevance
“…Psychoanalytic schools of thought have investigated the genesis of borderline pathology. As early as the 1940s Mahler et al. (1949) identified a group of children presenting with ego and object relational pathology far more severe than neurotic children, whilst less severe than those children diagnosed with psychotic disorders.…”
Section: Psychodynamic Understandings Of Borderline Pathologymentioning
confidence: 99%
See 1 more Smart Citation
“…Psychoanalytic schools of thought have investigated the genesis of borderline pathology. As early as the 1940s Mahler et al. (1949) identified a group of children presenting with ego and object relational pathology far more severe than neurotic children, whilst less severe than those children diagnosed with psychotic disorders.…”
Section: Psychodynamic Understandings Of Borderline Pathologymentioning
confidence: 99%
“…Psychoanalytic schools of thought have investigated the genesis of borderline pathology. As early as the 1940s Mahler et al (1949) identified a group of children presenting with ego and object relational pathology far more severe than neurotic children, whilst less severe than those children diagnosed with psychotic disorders. This led to speculation by Mahler and colleagues that they were witnessing the early prodromal phases of later schizophrenic disorders with the borderline psychopathology the earliest overt symptoms that could be identified.…”
Section: Psychodynamic Understandings Of Borderline Pathologymentioning
confidence: 99%
“…Dereistic thinking, feeling and action may be evident. These may be seen in the other syndromes and consist of "the direct manifestations of the primary process, the id, appearing on the surface of behaviour" (17). They are thus determined by inner meanings and considerations and appear illogical and strange to the normal observer who cannot understand them.…”
Section: Symbiotic Infantile Psychosismentioning
confidence: 99%
“…Sometimes the child was known to be schizophrenic previously and passes from the earlier state into one of pseudo neurotic schizophrenia. More commonly there is sub-acute illness manifesting up to about the tenth year (17) and no serious concern about the child may have been expressed previously.…”
Section: Pseudoneurotic Scbizopbreniamentioning
confidence: 99%
“…Other writers have relied less on symptom description and more on underlying dynamics formulated from psychoanalytic and object relations theories to delineate borderline conditions in children (Mahler, Ross, & De Fries, 1949; Pine, 1974;Leichtman & Shapiro, 1983). They suggested that such children have lacked early mother nurturance necessary for appropriate development.…”
mentioning
confidence: 98%